The Effect of Parental Attention and Provision of Educational Game Tools on the Beginning Reading Ability of Children Aged 4-5 Years - Fatimah, Fatimah; Sunardi, Nurita; Supriyadi, Supriyadi (IJBLE Scientific Publications Community Inc., 2025)
This study investigates the influence of parental attention and the provision of Educational Play Tools (EPT) on the early reading skills of children aged 4-5 years. The results demonstrate that parental involvement, specifically through active participation in learning activities, significantly contributes to the creation of an environment that fosters early literacy development. Additionally, the provision of Educational Play Tools offers an interactive and engaging learning experience, which further supports the enhancement of reading skills in young children. The findings underscore the importance of a synergistic relationship between parental attention and the availability of Educational Play Tools in establishing a robust literacy foundation during early childhood. Based on these findings, it is recommended that parents increase their engagement in their children’s educational activities and provide EPT that align with the developmental needs of the child. Moreover, the study calls for policies by government and educational institutions to ensure equitable access to high-quality Educational Play Tools, thereby maximizing their impact across diverse socio-economic groups.